ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi pada LKPD Kabupaten/Kota Provinsi Jawa Tengah 2010-2012) - Heri Atapson V Girsang; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2015)
This study aims to analyze the influence of some factors on disclosure level of Local Government Financial Report (LGFR) District/City of Central Java Province. The factors used in this study are the size of the local government, the financial self-sufficiency ratio of the local government, functional differentiation of the local government, debt financing of the local government, intergovernmental revenue of local governments, and the age of the of the local government.            The disclosure level of Local Government Financial Report (LGFR) calculated by counting the adherence of disclosure to the Government Accounting Standards and Permendagri No. 13 of 2006. The analytical method used is data panel regression. This research’s sample consisted of 105 LGFR district/city along 2010-2012 audited by Audit Board of the Republic of Indonesia Representative of Central Java Province. Data were obtained from the Audit Board of the Republic of Indonesia Central Java Province Representative. The results showed that the size of the local government, the financial self-sufficiency ratio of the local government, functional differentiation of the local government, debt financing of the local government, intergovernmental revenue of local government, and the age of the of the local government are proved to have no significant influence on the disclosure level of Local Government Financial Report (LGFR) District/City of Central Java Province.